2013
DOI: 10.1111/aab.12020
|View full text |Cite
|
Sign up to set email alerts
|

A new clade of Dickeya spp. plays a major role in potato blackleg outbreaks in North Finland

Abstract: Until recently Dickeya was regarded as a pathogen not established in Finland. As a result the blackleg symptom observed on potato was often associated with Pectobacterium atrosepticum. The occurrence of Dickeya spp. on potato in Finland was first reported in 2004. Since then the prevalence of Dickeya has been monitored through surveys and routine test of seed lots produced in the country. The results of monitoring of Dickeya spp. in seed lots produced in Finland between the years 2004 and 2008 indicated a stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 22 publications
(52 reference statements)
3
68
0
Order By: Relevance
“…The importance of the geographical orgin and the temperature profiles. This finding confirms the results of Degefu et al (2013) and van der Wolf et al (2014), that also indicated high similarities between D. solani strains of different origin. The variable tandem repeats method applied by Parkinson et al (2015) Parkinson et al (2015).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The importance of the geographical orgin and the temperature profiles. This finding confirms the results of Degefu et al (2013) and van der Wolf et al (2014), that also indicated high similarities between D. solani strains of different origin. The variable tandem repeats method applied by Parkinson et al (2015) Parkinson et al (2015).…”
Section: Discussionsupporting
confidence: 92%
“…The RFLP -PFGE was performed as already described by Degefu et al (2013). After the electrophoresis run was completed, the gels were stained with ethidium bromide solution (0.5 mg ml…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations